Phylogenetic Relationships of Southern African West Nile Virus Isolates - Burt, Felicity J.; Grobbelaar, Antoinette A.; Leman, Patricia A.; Anthony, Fiona S.; Gibson, Georgina V.F.; Swanepoel, Robert (Emerging infectious diseases, 2002)
Phylogenetic relationships were examined for 29 southern African West Nile virus (formal name West Nile virus [WNV]) isolates from various sources in four countries from 1958 to 2001. In addition, sequence data were retrieved from GenBank for another 23 WNV isolates and Kunjin and Japanese encephalitis viruses. All isolates belonged to two lineages. Lineage 1 isolates were from central and North Africa, Europe, Israel, and North America; lineage 2 isolates were from central and southern Africa and Madagascar. No strict correlation existed between grouping and source of virus isolate, pathogenicity, geographic distribution, or year of isolation. Some southern African isolates have been associated with encephalitis in a human, a horse, and a dog and with fatal hepatitis in a human and death of an ostrich chick.